(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
"National color" is tempered from the process of historical civilization, and modern times. In ancient times, the Qin Dynasty advocated black, and the atmosphere was simple; the Northern and Southern Dynasties advocated blue, which was bright and flying; the Song Dynasty advocated "preserving natural principles and removing human desires", fresh and elegant Green has become the mainstream; in addition, yellow, which symbolizes imperial power, and the majestic Chinese red have always been the national colors that will never fade in the hearts of the Chinese nation.